GE_GERICHTE P/3560/2017 vom 16. Januar 2020 - GE Cour de justice (2020)
APPRÉCIATION DES PREUVES;INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE;TORT MORAL;CONCOURS RÉEL | CP.189; CP.49.al1; CP.49.al2; CP.60; CPP.104